Identification of Effective Factors in Planning the Architecture of Cultural Centers Based on the Strengthening of Social Interactions of Citizens - rezvane mansori; Arash Saghafi Asl (تحقیقات کاربردی علوم جغرافیایی)
With the expansion of the population and the increase in the level of social needs of mankind to provide a better life, as well as the constraints facing humans in residential space, the necessity of being in communal spaces is very important. Because of having a variety of programs and other functions, cultural spaces create a good place for social interaction. As a result, attention to the social dimension of space in the design of cultural buildings and the relationship between space qualities and social concepts, including socialization, are of great importance in the success of these spaces. The purpose of this article is to study the factors influencing the design of contemporary cultural collections of the country and its relationship with social interactions in these collections. In this article, descriptive-analytic research methodology and also descriptions of these stages and processes of research are used for observing instruments, library studies and documents. Research results refer to social, physical and environmental factors and their implications for design.